Analysis of Pile Foundation Bearing Capacity and Soil Classification in Padang City - Silvianengsih; Mahardika, Tiara; M, Bagaskoro; Abddilah, Farizi; Liliwarti (SOTVI, 2024)
Padang City, west of Sumatra, is highly vulnerable to natural disasters such as earthquakes, landslides, and floods. The soil conditions in this area, consisting of tuff, silica, and rocks with low cohesion, pose challenges due to their weak bearing capacity, increasing the risk of ground movement or subsidence. This study analyzes the bearing capacity of pile foundations and soil classification in the Sungai Sapih area using the Cone Penetration Test (CPT) method and soil classification based on the Bagemann method. Investigations were conducted at five sounding points (S1–S5) in Sungai Sapih to understand the soil characteristics and provide optimal foundation planning recommendations. The results of this study indicate that the soil layers are dominated by clay, with variations such as organic clay, very stiff clay, and clay loam, all of which tend to have low end-bearing capacity. At depths of up to 11 meters, the cone resistance (qc) values were very low at all points, indicating that the pile foundation cannot rely on end-bearing support at this depth. However, increased friction along the pile shaft significantly contributes to the ultimate bearing capacity of the pile foundation. Hard soil layers were identified at depths of 12–16 meters, with qc values of approximately 150 kg/cm², providing a reference for deep foundation design. Based on the result of this study, the use of piles foundation and bored piles is recommended to reach the hard soil layers to ensure structural stability. Additionally, an analysis of soil settlement is necessary due to the high potential for deformation in the clay layers. This study is expected to serve as a guideline for safe and sustainable foundation planning in the Sungai Sapih area, rapidly developing as a center for government and public facilities in Padang City.